ENFORCEMENT OF CRIMINAL LAW AGAINST ACTS OF DESTRUCTION AND BEGGARS IN THE CITY OF MEDAN - Andika Cahaya Putro (NOMOI Law Review, 2022)
The existence of homeless people and beggars has become a part of life in big cities in Indonesia, especially in the city of Medan. Homeless and beggars are often seen on the side of the road to beg in public, it has become an option for them for people who cannot compete in the midst of public life for certain reasons. The nature of the research material used in completing this research is descriptive analysis that leads to normative juridical law research or doctrinal legal research, namely a research conducted or aimed only at written regulations or other legal materials. And the factors behind vagabonds and beggars in public places are; Migrating with desperate capital, lazy to try, physically disabled, lack of job opportunities, and others. The implementation of law enforcement can be carried out if it is indicated to have committed a criminal act, this is in accordance with Article 10 of the Regulation of the Head of the State Police of the Republic of Indonesia Number 14 of 2017 concerning Handling Homeless and Beggars. And if there are no elements of a criminal act, the Social Service will provide guidanceKeywords: Poverty, Homeless, Law Enforcement.